Russian and Polish Grammars of the 18th Century as Textbooks on Language Theory - Kozhinowa, Alla (Slavistica Vilnensis, 2020)
The article presents Russian and Polish grammarians’ points of view (Vasily Adodurov, Mikhail Lomonosov, Anton Barsov, Walenty Szylarski, Onufry Kopczyński) on considering language theory issues and how they described them in their works written in the 18th and early 19th centuries. The grammars under consideration were aimed not only at a detailed description of the Russian and Polish languages or teaching the correct language usage; in addition, they contained some theoretical information given in a manner that is comparable with modern linguistic knowledge. That information lay in the field of linguistic typology. It was also assumed that a language could acquire communicative, cognitive, nominative, and poetic functions (the appropriate terms were not used at that time). Besides, the issues concerning the forms of language existence – written and oral, as well as the dichotomy of language and speech, the nature of a language sign, including the ideas about its arbitrariness, its semantics and pragmatics were raised. Additionally, interesting discussions about sign relations at the phonetic-phonological language level, as well as some ideas of functional syntax were initiated. The results of the study lead to the conclusion that the grammars of the 18th century were a reflection of the historical situation in which this grammatical research was done.